Solving or not solving problems - Ferguson, Jenanne (My University, 2021)
The three articles featured in this issue may not appear to be related, but within their varying contexts, I found myself teasing out several chords that resonate throughout them, and one, in particular, struck me as notable. Directly or indirectly, these articles (as well as the report) all address the notion of problem-solving in some shape or form. Whether a historical account of protest as an attempt to solve issues of discontent among fur trade workers in Russian America, approaches to discussing climate change in northeastern Siberia, coping with failing infrastructure and the negotiation of corporate versus state responsibility—or dealing with COVID lockdowns and scholarly knowledge exchange at present—the articles in this issue all explore the confrontation of problems and how they might be solved.
Keywords: problem-solving; Siberian studies